2021
DOI: 10.1371/journal.pone.0249561
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and associated risk factors in patients with blood culture positive sepsis and acute kidney injury requiring continuous renal replacement therapy—A retrospective study

Abstract: Objectives Septic acute kidney injury (AKI) requiring continuous renal replacement therapy (CRRT) carries a mortality risk nearing 50%. Risk factors associated with mortality in AKI patients undergoing CRRT with blood culture positive sepsis remain unclear as sepsis has been defined according to consensus criteria in previous studies. Methods Risk factors associated with intensive care unit (ICU), 90-day and overall mortality were studied in a retrospective cohort of 126 patients with blood culture positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…CRP was also identified as a predictor of mortality, together with leukocyte count and ferritin. Similar results were achieved to those of previous studies [30].…”
Section: Discussionsupporting
confidence: 92%
“…CRP was also identified as a predictor of mortality, together with leukocyte count and ferritin. Similar results were achieved to those of previous studies [30].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, AKI in patients with sepsis has been associated with prolonged ICU and hospital stays in survivors [ 27 , 30 ]. Risk factors for mortality in patients with septic AKI, as with sepsis alone, have included older age, comorbidities, higher disease severity and decreased urine output [ 34 , 35 ]. Nonetheless, a recovery of renal function has been observed in up to 40% of patients that survive septic AKI.…”
Section: Acute Kidney Injury In Sepsis and Septic Shockmentioning
confidence: 99%
“…Although hyperlactatemia of > 2 mmol/L is criterion of septic shock according to the Sepsis-3, it is not mandated as a criterion of sepsis [31]. It has been reported that hyperlactatemia is an independent mortality predictor in patients with SA-AKI in the emergency department [38], postoperative AKI requiring RRT [25] and SA-AKI requiring CRRT [10]. However, other studies have shown that the initial lactate level is not independently associated with death in patients with SA-AKI requiring CRRT [37] or post-cardiovascular surgery AKI [28].…”
Section: Hyperlactatemia and Outcomesmentioning
confidence: 99%
“…Whether serum lactate levels are independently associated with mortality or kidney recovery after AKI remains controversial [10,25,28,37,38]. Thus, we applied a multivariable Cox proportional hazards model and included all variables listed in Table 1 to identify factors associated with mortality after dialysis-requiring SA-AKI.…”
Section: Pre-dialysis Hyperlactatemia Predicts Death and Dialysis Dependencementioning
confidence: 99%
See 1 more Smart Citation